EVALUATING THE IMPLEMENTATION OF CHARACTER EDUCATION REINFORCEMENT TO ATTAIN MENTAL REVOLTUION VALUE AT SD MUHAMMADIYAH PERUMNAS MAKASSAR - Muh. Ramli; Syarifuddin; Azis Muslimin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This thesis discussed the implementation of the values of character education at SD Muhammadiyah Makassar. The objectives of this study were (1) to observe the implementation of character education in achieving the goals of mental revolution values at SD Muhammadiyah Perumnas Makassar, (2) to observe the values of mental revolution applied at SD Muhammadiyah Perumnas Makassar, and (3) to observe the results of implementing the values of character education at SD Muhammadiyah Perumnas. The type of this research was qualitative research with descriptive analysis. This research was conducted at SD Muhammadiyah Perumnas Makassar. The data sources in this study included primary data, namely the vice principal, teachers, and students, and secondary data such as documents related to the object under study. Data were obtained through observation, interviews, and documentation. The data were then analyzed qualitatively by using triangulation to ensure validity of the data against the focus under study. The results showed that the values of character education integrated in the learning process included being religious, disciplined, diligent, curious, caring, and responsible. Meanwhile, the implementation of character education values in extracurricular activities was carried out through sacred tread activities, sports, and enrichment by providing motivation, understanding, advice, sanctions, role models, and rewards to students. As the implication, SD Muhammadiyah Perumnas Makassar further enhanced the implementation of character education values in order to realize a mental revolution program both in the learning process or intracurricular activities and extracurricular activities to create a generation of people with high moral integrity.